Heart Speaks unto Heart On the Kinship of Spirit and Thought: John Henry Newman and Edith Stein - Kłos, Jan (Philosophy and Religion, 2021)
Both Newman and Stein present a mature response to the challenges of their eras. In like manner they reflect splendid examples of genuine persons in the grip of disrupting cultural trends. They show the primacy of individual conscience and the importance of individual integrity even at the expense of social ostracism and extermination. Newman and Stein are outstanding witnesses of individual freedom vis-à-vis social and political systems. This book uniquely combines the biographies of these two figures in order to show that no matter what kind of circumstances we may live in, loyalty to one's own self is the most significant part of life. "In a penetrating account of Newman and Edith Stein, Jan Kłos explores the spirituality of two saints, each of them 'speaking to our time'. By explorations of their life and work, the author provides a wealth of insights for the twenty-first century. At once sensitive and learned, Jan Kłos's Heart Speaks unto Heart is a volume to be treasured and read again." - Prof. Andrew Breeze, Universidad de Navarra, Spain "In this profound and stimulating study, Kłos invites the reader to think, not so much about Newman and Stein as with them, and thus join them in their unique but mutually illuminating efforts to make sense of their faith, their times (still very much our times), themselves, and, ultimately, the mystery of the truth in whose grasp they both lived and died. In translating Newman's work, Stein discovered herself in communion with him. Heart Speaks unto Heart beautifully explores this communion, and in doing so shows us why it matters." - Prof. Paul Wojda, University of St. Thomas, U.S.A.. Readership: This book is addressed to readers interested in philosophy, moral philosophy, phenomenology and religion. It focuses on the individual person in his or her search for genuine identity. Philosophers, theologians, and psychologists would certainly find here a rich source of inspiration, especially when it comes to the individual when confronted with the quest of finding their true self.